Conservation of the Drosophila lateral inhibition pathway in human lung cancer: A hairy-related protein (HES-1) directly represses achaete-scute homolog-1 expression - Chen, Herbert (The National Academy of Sciences of the USA, 1997)
The achaete-scute genes encode essential transcription factors in normal Drosophila and vertebrate nervous system development. Human achaete-scute homolog-1 (hASH1) is constitutively expressed in a human lung cancer with neuroendocrine (NE) features, small cell lung cancer (SCLC), and is essential for development of the normal pulmonary NE cells that most resemble this neoplasm. Mechanisms regulating achaete-scute homolog expression outside of Drosophila are presently unclear, either in the context of the developing nervous system or in normal or neoplastic cells with NE features. We now provide evidence that the protein hairy-enhancer-of-split-1 (HES-1) acts in a similar manner as its Drosophila homolog, hairy, to transcriptionally repress achaete-scute expression. HES-1 protein is detected at abundant levels in most non-NE human lung cancer cell lines which lack hASH1 but is virtually absent in hASH1-expressing lung cancer cells. Moreover, induction of HES-1 in a SCLC cell line down-regulates endogenous hASH1 gene expression. The repressive effect of HES-1 is directly mediated by binding of the protein to a class C site in the hASH1 promoter. Thus, a key part of the process that determines neural fate in Drosophila is conserved in human lung cancer cells. Furthermore, modulation of this pathway may underlie the constitutive hASH1 expression seen in NE tumors such as SCLC, the most virulent human lung cancer.